An Investigation into the Thermal Properties of Termite Mound Clay Applicable to Grain Silo Construction (2015)
Provision of suitable grain silos in humid tropical climates has generated research interests on the possibility of using local materials for construction. Termite mound clay (TMC), a material available in abundance was investigated as a potential construction material. A major factor determining the suitability of construction materials for grain silos is its thermal properties. Therefore, thermal conductivity, specific heat capacity, thermal diffusivity and thermal mass of TMC were determined and compared with those of concrete and stainless steel which are commonly used for silo construction. TMC was collected, crushed and sieved using a 500pm sieve to remove coarse particles and foreign materials. The TMC powder obtained was mixed with water using volumetric ratio of 1:5 (i.e. water to clay) after which the thoroughly mixed clay was carefully fed into the mould and left to air-dry for 5 days. The samples were dried in the oven at 105oC for about 48 hours to remove all the moisture. Results revealed that thermal conductivity ranged from 0.17 to 0.24 W/(mK) with an average value of 0.21 compared to concrete and steel which range between 0.8 - 1.28 and 16.3 - 16.7 W/(mK) respectively. Specific heat capacity had an average value of 2576.94 J/(kgK) compared with concrete and steel which had values of 960 and 490 J/(kgK) respectively. Thermal diffusivity had a mean value of 1.47*10-8 m2/s in comparison to concrete and steel whose calculated values were 6.63 ><10-7 and 4.18 ><10-6 kJ/(m3 K) respectively while thermal mass had a mean value of 4723.5 kJ/(m3 K) compared to 2112.0 and 3831.8 kJ/(m3K) for concrete and steel respectively. It was concluded that TMC offers a thermally suitable alternative to these two for grain silo construction in the humid tropics.